The democratization of the system between political awareness and political upbringing in traditional society - Abd, Aqeel (Al-Adab Journal, 2023)
This research has focused his studies on the most important thing going through Arab and regional societies, including the Iraqi society from the political and social transformations, economic and cultural result of regime change toward democratic model for the institutions of power under proven and traditional and other social institutions and its adherence to traditional culture adopts frameworks, ideas and methods of upbringing secrete an individual and a group of consciousness politician depends on inherited historical pattern of social relations between the components of society as well as the relationship between those groups and political power make democracy is just a theory is viable concepts and realistic because it contradicts with the nature of the social system, structures and formats constituent ideas only if the worker community with those concepts and insert it into the cultural his system fueled by its members through socialization and this is what suffers our communities from not having to keep the gap between the political system evolution theory forward and setback of the community about the roots of traditional culture to protect the cultural identity and social specificity of the concepts developed by the outsider it does not fit the nature or social structure, trying to amend these concepts and adapted commensurate with perceptions to produce a political and social system and hybrid.